동해안 삼척 호산에 서식하는 둥근성게 Strongylocentrotus nudus의 분포와 피식 패턴 - 유재원; 손용수; 이창근; 김정수; 한창훈; 김창수; 문영봉; 김동삼; 홍재상 (Pada (Hanʼguk Haeyang Hakhoe), 2004)
An ecological study on a sea urchin population, Strongylocentrotus nudus, a key role species in recovery of macroalgal bed, was conducted in Hosan, Samcheok area on the east coast of Korea. Three experimental plots, namely, AMB (artificially-restored macroalgal bed), BG (barren grounds) and NMB (natural macroalgal bed) were established after a pilot survey in June 2002. Distribution and abundance, grazing rates, predation pressure and predator guilds on S. nudus were estimated in three plots bimonthly from Aug. to Dec., 2002. Abundance of S. nudus was lowest, but median test diameter of the urchin was highest (Kruskal-Wallis test, p-value, p<0.001 in Aug. and p=0.003 in Oct.) in NMB In-situ grazing rate of S. nudus estimated by enclosure cage experiment in NMB was about 12 times higher in Aug. (160.0 mg seaweed/g sea urchin/day) than in Oct. (13.8). Predation intensity measured by tethering experiment was higher in NMB. Most of the predators on S. nudus were invertebrates and no fish predators were found. Predator guilds identified by the fish trap experiment using live or dead sea urchins included who]ks Neptunea arthritica, starfish Asterina pectinifera, hermit crabs Pagurus of. samuelis, Paguristes barbatus, brown shawl crabs Atergatis integerrimus and crabs Actaea subglobosa. High predation pressure on S. nudus in natural macroalgal beds was the likely cause of its low density. Elevated sea urchin density and the consequent lasting deforestation of macroalgae in barren grounds demonstrate the importance of predation pressure on sea urchins. 강원도 삼척 호산해역에서 해조장의 회복에 결정적 역할을 할 것으로 짐작되는 둥근성게(Strongylocentrotusnudus) 개체군에 대한 생태학적 연구를 수행하였다. 2002년 6월의 예비연구를 통해 조하대에 3개 실험구(인공해조장. 갯녹음지역, 자연해조장)를 설정하고, 8월, 10월, 12월에 둥근성게의 분포와 섭식률, 포식압, 포식자 조합을 추정하였다. 둥근성게의 서식 밀도는 자연해조장에서 가장 낮았으나, 각경(test diameter)의 중위수는 가장 큰것(Kruskal-Wallis test, 8월, p<0.001; 10월, p=0.036)으로 나타났다. 둥근 성게의 먹이 섭식률을 추정하기 위한 실험(enclosure cage experiment)은 자연해조장에서 수행되었으며, 8월과 10월에 각각 160, 13.8 mg seaweed/g sea urchin/day로 추정되었다. 둥근성게에 대한 상대적인 포식압의 실험구 간 비교를 위해 수행된 포박실험 (tethering experiment)으로부터 자연해조장의 포식압이 다른 두 실험구에 비해 상대적으로 높은 것으로 나타났다. 실험 도중 현장에서 관찰된 포식자는 대부분 무척추동물인 것으로 나타났으며 어류 포식의 증거는 찾을 수 없었다. 죽은 성게나 산 성게를 담은 통발을 이용하여 포식자 조합을 파악하기 위한 실험을 하였다. 둥근성게의 포식자는 복족류 Neptuned arthritica와 별불가사리 Asterina pectinifera, 집게류 Pagurus cf. samuelis, 그리고 게류에 속하는 Atergatis integerrimus 등이며, 집게류인 Paguristes barbatus와 게류인 Actaea subglobosa도 가능성이 있는 포식자인 것으로 추정되었다 실험구 간 대비되는 관찰 결과로부터 (1)성게의 낮은 서식 밀도와 관련된 요인은 포식압이며, (2) 이는 조사 해역의 백화 현상의 발생, 유지와 낮은 포식압 간 가능한 상관관계를 제시하는 것으로 해석되었다.